The art of transformation: art, marriage, and freedom in The lady from the sea - Moi, Toril (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2009)
The play, The Lady from the Sea, sets out to provide an answer to the question: namely, what it takes for a relationship to become a marriage. In order to follow Ibsen’s analysis of this question, however, we also need to notice that the play can be read as Ibsen’s rebuff to romantic tales of female sacrifice. The play also intertwines the story of Ellida’s achievement of freedom with an investigation of art, theatre, and music, in which the main question is how painting, sculpture, and theatre can express what some critics have called the “inner mind”. —————————————————————————————————- A ARTE DA TRANSFORMAÇÃO: ARTE, CASAMENTO E LIBERDADE EM THE LADY FROM THE SEA A peça, The Lady from the Sea, se propõe responder a pergunta: o que é necessário para uma relação tornar-se um casamento. Entretanto, para acompanhar a análise que Ibsen faz da questão, precisamos observar que a peça pode ser lida como uma crítica de Ibsen às fábulas românticas de sacrifício feminino. A peça também entrelaça a história das conquistas de liberdade de Ellida com uma investigação de arte, teatro e música, em que a questão principal é como a pintura, a escultura e o teatro podem expressar aquilo que a crítica chama de “espírito interior”. — Artigo em inglês.